Addressing elder abuse through integrating law into health: What do allied health professionals at a Community Health Service in Melbourne, Australia, think?. (17th September 2019) - Lewis, Virginia J.; White, Vanessa; Hawthorne, Faith; Eastwood, Jess; Mullins, Robyn
Abstract: This research looked at the attitudes of Community Health Service (CHS) staff regarding the integration of a lawyer into their CHS both before and after the integration occurred. It assessed their confidence in identifying and addressing elder abuse at each point. A written survey was distributed to staff before the lawyer commenced (n = 126), and approximately 12 months afterwards (n = 54). The preliminary survey demonstrated widespread agreement that legal issues can affect older people and supported having a lawyer in a CHS. Respondents were not confident about their capacity to identify abuse and provide referrals to a lawyer, but this improved in the follow‐up survey. These CHS staff were aware of the potential impacts of elder abuse and supported embedding a lawyer in the health service. Information and training as part of this service model should focus on the skills needed for CHS staff to play their role in such a partnership.